Implementation of Accreditation-Based Education Quality Assurance System at SMP Santa Lusia Sei Rotan - Hotmaida Sidabutar; Syawal Gultom; Darwin Darwin; Yuniarto Mudji Susatyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to develop the implementation of an accreditation-based educational quality assurance system at SMP Santa Lucia Sei Rotan. The samples used in this study were observations, interviews, and documentation conducted by teachers of SMP Santa Lucia Sei Rotan. The research method used is research and development using descriptive qualitative field research. The results of the research are in the form of a module for implementing an accreditation-based education quality assurance system at SMP Santa Lucia Sei Rotan. The assessment results from colleagues obtained 87.25% in the good category. The results of the module design validation by the design experts were 94.5% with very good criteria. The results of the validation of teaching materials by material experts were 97.33% with very good criteria.